Interpretation Of Human Tragedies in Edgar Allan Po Stories - Khalimov Salokhiddin Samievich (Zien Journals, 2022)
This article analyzes the story of the Ligeia, which played an important role in the work of Edgar Allan Poe, one of the great figures of world literature, and is directly related to his autobiography. The ideological pathos of this story, the post-accident interpretations of Ligeia, which can be called the second part of the plot system, is a very complex and painful study of the "dialectic of the heart".
Keywords: Human psyche; dialectics of the heart; artistic emblem; Ligeia